Theoretical Integration and Localized Practice: Implementing Creative Music Pedagogy within the National Curriculum Framework in Handan's Primary Schools - Song Jieyi; Suraya Amirrudin (Ilmu Inovasi Nusantara, 2026)
This research examines the implementation of creative music pedagogy within China's national curriculum framework through a qualitative investigation of four primary schools in Handan, addressing tensions between standardized educational requirements and innovative pedagogical approaches. Using interpretive phenomenological analysis, the study involved 10 music educators and 3 administrators through semi-structured interviews, participant observation, and document analysis over 6 months. The investigation reveals that teacher adaptation follows a predictable five-phase developmental pathway, requiring 12 to 18 months for sustainable integration, progressing from initial resistance to strategic coordination. Cultural embedding involves complex negotiations as educators integrate local opera traditions and folk music elements within standardized frameworks, while sophisticated coordination strategies emerge, particularly